Lima Kode Roland Barthes dalam Cerpen Jangan Kau Beli Rumah Itu Karya K. Usman - Diana, Jumianti (Ruang Kata, 2025)
This study aims to present the mode of transactional messages contained in the short story Jangan Kau Beli Rumah Itu (Don’t Buy That House) by K. Usman. The research method used in this study is descriptive qualitative research. Data collection was carried out through literature review techniques, namely observation and note-taking. Data analysis was conducted using the five codes proposed by Roland Barthes. The research findings yielded a total of nineteen data points. Four data points related to the hermeneutic code reveal the mysterious presence of the character Gurun, whose identity remains unknown and whose absence during congregational prayers at the mosque is perceived as unusual by the worshippers. Three data points related to the connotative code illustrate figurative expressions reflecting the absence of Gurun, the congregation's boredom due to repetitive and uninspiring sermons, and a metaphor suggesting that preachers should study harder from various teachers and sources. Three data points concerning the symbolic code indicate the presence of three symbols: statues or monuments representing individuals who refuse to learn and thus possess stagnant knowledge; full-grown rice grains symbolizing humility; and evening time representing old age. Seven data points related to the action code highlight active actions performed by characters in the short story. Two data points related to the cultural code refer to the respect a son-in-law shows to his in-laws and to Gurun's religious knowledge and steadfast faith. The main message conveyed in the story emphasizes the importance of preserving one's faith